Answer:
the vertex is:
(2, -1)
Explanation:
First solve the equation for the variable y
![x^2-16y-4x-12=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/hxwoh9004lk4abhiuaf5erm7nltxh5fue3.png)
Add 16y on both sides of the equation
![16y=x^2-16y+16y-4x-12](https://img.qammunity.org/2020/formulas/mathematics/high-school/nv423yrvb07m17smco6sf1wfgff84omege.png)
![16y=x^2-4x-12](https://img.qammunity.org/2020/formulas/mathematics/high-school/n9vfqeb7ihv2z36mravoiajgd6r5rqlhtn.png)
Notice that now the equation has the general form of a parabola
![ax^2 +bx +c](https://img.qammunity.org/2020/formulas/mathematics/middle-school/365cnh1co3bh8nuwu6jy5u7pyu8etmydg1.png)
In this case
![a=1\\b=-4\\c=-12](https://img.qammunity.org/2020/formulas/mathematics/high-school/bxeov7l9qmzcoctjy9anhtparyi9ij13ha.png)
Add
and subtract
on the right side of the equation
![16y=(x^2-4x+4)-4-12](https://img.qammunity.org/2020/formulas/mathematics/high-school/eo9xjywwfp3gehdkhp3gwqxk063lj799zl.png)
Factor the expression that is inside the parentheses
![16y=(x-2)^2-16](https://img.qammunity.org/2020/formulas/mathematics/high-school/m8jdgxg1ss1st3q0nmk751ebawoybsb3p5.png)
Divide both sides of the equality between 16
![(16)/(16)y=(1)/(16)(x-2)^2-(16)/(16)](https://img.qammunity.org/2020/formulas/mathematics/high-school/gf3nx8ko2kodcveyktoboxjiorqm4d0tkd.png)
![y=(1)/(16)(x-2)^2-1](https://img.qammunity.org/2020/formulas/mathematics/high-school/koi714nax2p0lkstkf35j31nfcvagusonr.png)
For an equation of the form
![y=a(x-h)^2 +k](https://img.qammunity.org/2020/formulas/mathematics/high-school/5phs59z04novphub3utz9iv762p2p16p9k.png)
the vertex is: (h, k)
In this case
![h=2\\k =-1](https://img.qammunity.org/2020/formulas/mathematics/high-school/5et0utmsimgej6g6mi4s2x09miiaucifwb.png)
the vertex is:
(2, -1)